JURIDICAL STUDY OF CHILDREN WHO WORK AS INFLUENCERS IN RECEIVING ENDORSEMENTS IN SOCIAL MEDIA - Nasanta, Ester; Wahyudi, Eko (Universitas Islam Balitar, 2024)
Child influencers are a profession that can channel the talents and interests of the child in positive terms, one of which is by receiving endorsements. Endorsement is a support in the form of cooperation between companies and celebrities/influencers by promoting a product produced by the company and bound by a valid agreement. As in Indonesia, many public figures raise their children to become influencers from an early age. In this case, what is the view of the child influencer profession according to positive law in Indonesia, bearing in mind that there are frequent reports of public figures suspected of exploiting children and their legal protection for child influencers in receiving endorsements on social media in the event of data leakage and default, both from the company or from the endorser himself. This study uses normative legal research methods, namely discussing the doctrine of legal facts, principles, norms, and principles in the science of law, which focuses on laws and regulations related to working children, electronic transaction systems, and child protection using a statutory approach. invitation or statue approach.. The results of this study explain the legal views regarding the child influencer profession according to positive law in Indonesia, which begins with the position of child influencers as endorsers, forms of legal violations that can occur when receiving endorsements on social media and legal protection efforts for child influencers as a whole. preventive and repressive.